ANTARA CINTA SEJATI DAN KEWAJIBAN SEJATI (IZIN NIKAH CAMPUR DAN KEWAJIBAN PENDIDIKAN ANAK SECARA KATOLIK DARI PERSPEKTIF HUKUM KANONIK) - Kelore, Damas (Jurnal Euntes, 2024)
This research focuses on the dynamics of child education in Disparitas Cultus from the Catholic doctrine perspective. The main challenge faced by couples in Disparitas Cultus is how to integrate two different beliefs while still promoting the obligation of the Catholic side to educate children in Catholicism without negating the freedom of the non-Catholic side. This research will explore how couples achieve harmony between their faiths, creating an environment where children can grow and develop spiritually. In addition, it will identify the challenges and concrete strategies faced by intermarried families in implementing Catholic teachings for children's education. This research is expected to provide in-depth insights into how intermarried families manage differences in beliefs and embrace Catholic values in their efforts to educate children holistically.